Improving Students’ Reading Comprehension of Narrative Text Through Storytelling Using Webtoon at First Grade of MA Daruttolibin Watumalang (International Journal of Education and Literature, 2026)
English is an international language that plays a vital role in education and technology; therefore, students are required to master reading comprehension skills, especially narrative texts, to face the challenges of globalization. This study, entitled "Improving Students' Reading Comprehension of Narrative Texts Through Storytelling Activities Using Webtoons in Grade I of MA Daruttholibin Watumalang," aims to improve students' reading comprehension of narrative texts through storytelling activities using Webtoons as a learning medium. This study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection. Data were collected using descriptive qualitative methods through interviews, tests, and classroom observations. The research procedure began with a pre-test, followed by the implementation of treatment and post-tests in each cycle. The findings indicate that the use of storytelling supported by Webtoons effectively improved students' reading comprehension. This improvement was reflected in students' increased learning motivation, better understanding of narrative text elements, and improved ability to accurately retell stories.